Penerapan Model Pembelajaran Student Teams Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Limit bagi Siswa Kelas XI MIPA 1 SMAN 3 Magelang - Yustinus Sumpana (Jurnal Syntax Transformation, 2021)
The purpose of this study is to describe the improvement of learning outcomes through the application of the Student Teams Achievement Division (STAD) Learning Model on the Limit material for students of class XI MIPA.1 SMAN 3 Magelang, the subject of the research is class XI MIPA 1 SMA Negeri 3 Magelang, with a total of 30 students. with details of 14 men and 16 women. This study uses a Classroom Action Research (CAR) approach with 2 cycles, this research was conducted as an effort to overcome the low learning outcomes. The object of research in this classroom action research are various activities that occur in the classroom during the learning process. Data collection techniques were carried out by observation, interviews, tests and documentation. While the data analysis used was descriptive qualitative and quantitative analysis. The results of this study show . the application of the Student Teams Achievement Division (STAD) learning method in Limit learning can improve student learning outcomes. The results of the student motivation questionnaire before the action (Pre-cycle) with a score of 46.11 with a less category increased to 60.56 with a sufficient category in the first cycle and increased to 84.44 with good category in cycle II. Learning outcomes before the action mean the value of 68.75 with 43.44% completeness learning to 77.83 with 66.67% learning completeness in the first cycle and becomes 85.28 with 80% completeness in the second cycle. The increase in learning mastery is Cycle I increased by 23.23% from Pre-cycle, while Cycle II increased 13.33% from Cycle I. Thus, the improvement of student learning outcomes through the application of the Student Teams Achievement Division (STAD) learning model can be proven true.